Quantitative elemental mapping of chondritic meteorites using laser ablation-inductively coupled plasma-time of flight-mass spectrometry (LA-ICP-TOF-MS). Issue 2 (17th January 2023) - Maeda, Ryoga; Van Acker, Thibaut; Vanhaecke, Frank; Yamaguchi, Akira; Debaille, Vinciane; Claeys, Phillippe; Goderis, Steven
Abstract : Fast-(semi)quantitative elemental mapping using state-of-the-art laser ablation-inductively coupled plasma-time of flight-mass spectrometry (LA-ICP-TOF-MS) was applied to a set of chondritic meteorite samples. Abstract : Fast elemental mapping using laser ablation-inductively coupled plasma-time of flight-mass spectrometry (LA-ICP-TOF-MS) was applied to a set of chondritic meteorite samples, more specifically H chondrites. LA-ICP-TOF-MS enables element distribution maps for both major and trace elements to be obtained at μm-order spatial resolution (5 × 5 μm square pixels in this study) in a (semi-)quantitative manner. To assess the reliability of the quantitative data as obtained using LA-ICP-TOF-MS mapping, the accuracy and precision as obtained using this fast elemental mapping approach were compared to those of the data obtained using the more conventional spot analysis with an electron probe micro analyzer and LA-ICP-sector field (SF)-MS for major and trace elements, respectively. The maps obtained using LA-ICP-TOF-MS visualize elemental distributions among the constituent minerals, while major and trace element abundances determined using LA-ICP-TOF-MS are overall in good agreement within up to 30% relative uncertainty with those obtained based on the spot analyses and with literature values. Yet, some analytical limitations of LA-ICP-TOF-MS mapping remain due to the limited ablated yield when using a small laser spot size for high spatial resolution mapping, while ICP-TOF-MS shows a lower sensitivity and narrower linear dynamic range than does ICP-SF-MS. On the other hand, the main host phase(s) of an element can be readily identified and the major and trace element abundances in the phase(s) can be quantified with an accuracy approaching that of the spot analyses. As such, this study demonstrates the potential of LA-ICP-TOF-MS for fast quantitative imaging of various types of samples, in particular geological samples.